Sifat Fisik Permukaan Resin Komposit Hybrid Setelah Direndam dalam Minuman Energi pH Asam - R Helal Soekartono; Anita Yuliati; Ratih Mutiara Sani; Dian Dwi Pratiwi (Jurnal Material Kedokteran Gigi, 2018)
Composite resins are becoming more popular in restorative dentistry, particularly because of their superior esthetic properties. Composite resin may suffer degradation over time, which can be predicted by microstructural changes on its surface due to acidic conditions. The purpose of this study was to evaluate the microstructural changes of the surface of hybrid resin composite after immersed in acidic energy drinks of pH 3,2; 3,7; and 3,9 for 2 hours. Hybrid resin composites were cured with LED light curing unit. Specimens of 2 mm depth and 7 mm diameter were divided into 3 experimentals and 1 control. Each experimental was immersed in different energy drinks with different pH respectively (pH 3,2; 3,7; 3,9) and the control was immersed in aquadest for 2 hours. The surface roughness was measured using surface roughness measuring instrument before and after immersion then the Microstructural changes were evaluated under a scanning electron microscope (SEM). Surface roughness measuring instrument and SEM analysis showed, the erosion and surface degradation to all 3 hybrid resin composites after being subjected to the experimental conditions. The surface of hybrid resin composite undergoes noticeable microstructural changes after being immersed in energy drinks of pH 3.2, 3.7 and 3.9 for 2 hours.